Evolution and trends in tourism conflict studies (2004-2024): a bibliometrics review - Yurong, Wu; Bidin, Sheena; Johari, Shazali (Malque Publishing, 2024)
As the global tourism industry has rapidly grown, tourist destinations are facing increasing environmental pressures, social conflicts, and cultural clashes. Tourism conflict has become one of the key issues hindering sustainable tourism development. This study aims to explore the research hotspots in tourism conflict studies, providing insights into current trends and future research directions. a comprehensive review of 804 research articles on tourism conflict is carried out based on bibliometric records from the Web of Science Core Collection database ranging from 2004 and 2024. Techniques such as coauthorship analysis, cocitation analysis, and keyword co-occurrence analysis using the CiteSpace software was employed for this review. The results reveal that China, the United States, the United Kingdom, and Australia are the major countries contributing to tourism conflict research. The research topics have evolved from perceptions to root causes, from case studies to patterns, and from phenomena to essence, gradually forming five main research topics: 1) the conceptual connotations and theoretical interpretations of conflict; 2) different conflict situations and typical cases; 3) causes of conflicts; 4) conflict governance;5) reflections on tourism conflicts from a sustainable perspective.This study provides insights into the current state, research hotspots, knowledge gaps, and future research directions in the field of tourism conflict, benefiting scholars, industry practitioners, and government agencies.